The Effectiveness of Letters Card Media in Writing Lontara’ Alphabet Makassar at SMP Negeri 1 Pallangga in Gowa District - Hamriani, Hamriani; Garim, Idawati; ., Usman (Lingua Cultura, 2016)
The purpose of this study was to explain the effectiveness of writing Lontara’ alphabet Makassar via letters card media in Class VII SMPN 1 Pallangga, Gowa district. This research used quantitative method. The steps was taken, namely (1) The initial test (pre-test) or measurement prior to treatment, (2) the implementation of the action (treatment), and (3) the measurement that was done after post- test. The object of this study was the students of Class VII students in SMP Negeri 1 Pallangga, while the selected students as sample were students of class VII-18 woth total 50 students. Data collection techniques used were participatory observation, test, and interviews. Data analysis techniques used include data description, the average similarity test, and requirements analysis test. The results show that learning by using letters card media is very effective. It can be seen from the results of post-test analysis which shows higher level of achievement by using a lontara’ alphabet Makassar letters card media compared to the pre-test. In addition, in learning process the students are more active by using the letter card media compared to not using these media. While other factors that influence the effectiveness of learning can be affected by three factors, they are motivation, educational qualifications of teachers, and the environment.